Navigating urban poverty: The role of livelihood capital in the livelihood strategies of urban beggars in Indonesia - Choirul Amin; Wahyu Tyas Pramono; Jumadi Jumadi; Dewi Novita Sari; Maxim G.M. Samson (Social Sciences and Humanities Open)
The global challenges of urban poverty and homelessness are widely considered among the most critical, with beggars usually symbolizing visible and marginalized groups of the urban poor. Using the Sustainable Livelihoods framework, this paper considers how livelihood capitals influence survival strategies among urban beggars in Surakarta, Indonesia. Key findings reveal that financial and social capital plays a significant role in developing an enabling environment to enhance the transition from begging to other non-begging livelihoods; financial stability diminishes one’s dependence on begging, whereas social networks become important access vehicles. Human capital, such as education and vocation, significantly diminishes dependence upon begging. Physical capital most often reinforces dependence by maintaining poverty traps. Surprisingly, environmental quality and physical health had a limited role since beggars are concerned about immediate survival rather than general well-being. A total of 150 beggars were recruited using the time-location sampling method. Out of these, 142 valid responses were analyzed. Different livelihood capitals were quantified through the entropy method, whereas their influence on livelihood strategy was analyzed using logistic regression models. Findings emphasize how such interventions are necessary to strengthen social support networks through community programs with NGO partnerships, expand access to microfinance against financial instability, and skill-building initiatives with appropriate relevance to urban beggars. These findings have operationalized policy insights for designing inclusive poverty alleviation strategies in the rapidly urbanizing context of addressing capital deficiencies and sustaining transitions.